Co-existence of the abdominal wall and thoracic endometriosis: case report and literature review - Gao, Bo; Li, Zhi; Liu, Hui; Zhou, Gongmin; Lai, Xiuxiu (Frontiers in Medicine, 2025)
Extra-pelvic endometriosis always presents complex diagnostic challenges due to its non-specific symptoms. We describe a rare case of coexisting iatrogenic abdominal wall endometriosis (AWE) and thoracic endometriosis (TE) in a 33-year-old woman without pelvic involvement. The patient, with a history of two cesarean sections, presented with chronic abdominal pain and an asymptomatic pulmonary nodule. Both lesions were removed through surgical resection and histologic examination confirmed endometriosis. One year after the surgery, the patient experienced a recurrence of the abdominal pain and opted for hormone therapy. In this case, AWE is consistent with iatrogenic endometrial transplantation, while the thoracic lesion may result from blood transmission after cesarean section, but the specific mechanism remains to be further explored. We aimed to provide a novel insight into the multifactorial pathogenesis of extrapelvic endometriosis and multidisciplinary management.